2003
DOI: 10.1113/jphysiol.2002.032367
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin‐proteasome‐dependent muscle proteolysis responds slowly to insulin release and refeeding in starved rats

Abstract: The central role of the ubiquitin‐proteasome system in the loss of skeletal muscle protein in many wasting conditions has been well established. However, it is unclear what factors are responsible for the suppression of this system during periods of protein gain. Thus, the aim of these studies was to examine the short‐term effects of insulin release and nutrients on skeletal muscle protein turnover in young rats starved for 48 h, and then infused intravenously with amino acids (AA), or fed an oral diet. Forty‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 65 publications
2
23
2
1
Order By: Relevance
“…In this system, proteins are first marked for degradation by chains of the polypeptide cofactor ubiquitin, and then recognized by the 26S proteasome which can degrade ubiquitinated proteins to small peptides [17,18]. In our study we observed a number of ubiquitin-related genes with different expression levels in wild and domestic chicken breeds (Table 2), indicating possible selection pressure on this specific function of genes.…”
Section: Domestication Driven Differential Expression Of Ubiquitin Rementioning
confidence: 60%
“…In this system, proteins are first marked for degradation by chains of the polypeptide cofactor ubiquitin, and then recognized by the 26S proteasome which can degrade ubiquitinated proteins to small peptides [17,18]. In our study we observed a number of ubiquitin-related genes with different expression levels in wild and domestic chicken breeds (Table 2), indicating possible selection pressure on this specific function of genes.…”
Section: Domestication Driven Differential Expression Of Ubiquitin Rementioning
confidence: 60%
“…4B). However, this return to baseline occurred only on day 2 of refeeding, which was 1 day after the normalization of rates of protein breakdown (17) but was simultaneous to the recovery of muscle mass, which increased to levels similar to those of fed controls on day 2 (Fig. 4A).…”
Section: Resultsmentioning
confidence: 97%
“…MAFbx and MuRF1 were first demonstrated in muscle atrophy, and were found to be overexpressed in most states involving muscle loss, including paralysis, starvation, diabetes, sepsis, renal failure, and glucocorticoid excess [1]. Previous studies suggested that many genes related to the ubiquitinproteasome system were upregulated by starvation, including 14-kD E2, calpain large subunits, and 20S proteasome subunits [4,9]. The current study demonstrated that, in accord with other components of the ubiquitin-proteasome system, the E3 ligases MAFbx and MuRF1 were significantly induced in chick skeletal muscle at both the RNA and protein levels following starvation for 12 and 24 h. Refeeding normalized the expression of these two genes.…”
Section: Discussionmentioning
confidence: 99%
“…MuRF1 is a muscle-specific RING-finger protein that binds the Cys-His zinc-binding motif [3]. MAFbx and MuRF1 are specifically expressed in cardiac and skeletal muscles and have vital roles in protein degradation during muscle wasting [4]. Numerous studies have demonstrated that the expression of these two genes is upregulated during processes that involve muscle wasting, including muscle atrophy, injury, burns, aging, chronic illness, and starvation [1, 5,6].…”
mentioning
confidence: 99%